Damage Mechanism in Counter Pairs Caused by Bionic Non-smoothed Surface - ZHANG Zhan-hui; WANG Yi-qiang; YE Guo-yun; HAN Zi-yuan; ZHANG Zhi-jie; LUO Hai-bo (Cailiao gongcheng, 2016)
Four biomimetic non-smoothed surface specimens with different shapes were prepared by laser processing. Tests were conducted on MMU-5G wear and abrasion test machine to study the influencing rule of non-smoothed surfaces on counter pairs. The results show that the mass loss of the friction pair matching with the non-smoothed units is much greater than the ones matching with the smooth specimens. The pairs matching with different non-smoothed units suffer differently. The non-smoothed surface protruding zone exerts micro cutting on counter pairs. The striation causes the greatest mass loss of the pairs than the other non-smoothed units, which almost doubles the damage of the grid ones suffering the least. The difference in pairs damage is attributed to the different mechanism of undertaking the load in the process of wear. The damage can be alleviated effectively by changing the shapes of the units without increasing or decreasing the area ratio of the non-smoothed units.